TINGKAT PENGETAHUAN KADER TENTANG PROGRAM JAMPERSAL PASCA SOSIALISASI DI WILAYAH KERJA PUSKESMAS KEPUTIH KELURAHAN KEPUTIH SURABAYA - Shofi, Btari Himmatus; Munjidah, Annif (Jurnal Ilmiah Kesehatan, 2014)
JAMPERSAL is a government program which is to decrease maternal death and fetal death. Based on first data from the result survey in 5 health volunteer of public hospital at the district Keputih public hospital about JAMPERSAL?s knowledge on May 2013 , there was 3 health volunteer who didn?t know about JAMPERSAL program. This research is to know the knowledge level of health volunteer about JAMPERSAL after getting a socialization. This research take place at the district of public hospital of Keputih Surabaya. The research design is using descriptif. The population is every health volunteer of public hospital who joined the socialization of JAMPERSAL at the district Keputih public hospital in 2013 are 20 people. This research are taken by using total sampling with one variable is knowledge level. The research data is primary data taken from quesioner which is fill by the repondent.The data will be processed with editing, scoring, coding, tabulating. Then the data will be analized in descriptif, after that it reserved in frequency distribution table and crossed. Then the next step is to explain the result in naratif. The result of this research is from 20 respondent, most of them ( 60% ) have an enough knowledge, (40%) less knowledge The conclusion of this research is almost health volunteer who had joined JAMPESAL socialization have an enough knowledge. A public health should be resosialization about JAMPERSAL program for health volunteer by using case study and leaflet.